Proses Pembuatan Busana Pesta Dengan Lukis Kain The Process Of Making Party Clothes With Fabric Painting - Edi Suwasana; Vayza Indah Febrianti (Akademi Kesejahteraan Sosial Ibu Kartini Semarang, 2024)
Party attire is clothing that is worn to attend the occasion of a party event. In party clothes, the addition of paintings on the cloth is given. Painting is the result of painting in the form of a display that has aesthetic value. This party dress design with the application of painting techniques with Dutch building ideas (windmills) gives the impression of symbolizing energy, strength, courage, love, struggle, and speed. Painting on cloth has quite a complexity in the process so it requires high precision and patience. This study uses the method of observation, interviews, documentation, literature. In this descriptive research, the data collected is in the form of words and pictures The results of making this report to find out the manufacture of party dresses with cloth painting. The process of making party dresses with cloth painting has 3 parts, namely on the right, left and back of this skirt through several stages, namely: 1) determining the design model, 2) Taking measurements, 3) preparing tools and materials, 4) making patterns, 5 ) cutting materials, 6) merging, 7) sewing, 8) finishing. The cloth painting process itself includes: 1) determining the painting design, 2) sketching the painting on the cloth, 3) preparing the painting material, 4) applying paint to the material, 5) painting on the cloth. In making cloth painting, you need a sketch to make it easier to work on. Suggestions in making clothes with cloth painting need to pay attention to paint so that the color of the paint and fabric on the dress looks good, so first select the color that matches the dress. To reduce the risk of paint drying easily and wasting paint, it's best when you go through the process of painting the fabric to paint the same color first, so that the results are maximized.